Morpholino gene knockdown in adult Fundulus heteroclitus: role of SGK1 in seawater acclimation. - Emily G Notch; Joseph R Shaw; Bonita A Coutermarsh; Marisa Dzioba; Bruce A Stanton (PLoS ONE)
The Atlantic killifish (Fundulus heteroclitus) is an environmental sentinel organism used extensively for studies on environmental toxicants and salt (NaCl) homeostasis. Previous research in our laboratory has shown that rapid acclimation of killifish to seawater is mediated by trafficking of CFTR chloride channels from intracellular vesicles to the plasma membrane in the opercular membrane within the first hour in seawater, which enhances chloride secretion into seawater, thereby contributing to salt homeostasis. Acute transition to seawater is also marked by an increase in both mRNA and protein levels of serum glucocorticoid kinase 1 (SGK1) within 15 minutes of transfer. Although the rise in SGK1 in gill and its functional analog, the opercular membrane, after seawater transfer precedes the increase in membrane CFTR, a direct role of SGK1 in elevating membrane CFTR has not been established in vivo. To test the hypothesis that SGK1 mediates the increase in plasma membrane CFTR we designed two functionally different vivo-morpholinos to knock down SGK1 in gill, and developed and validated a vivo-morpholino knock down technique for adult killifish. Injection (intraperitoneal, IP) of the splice blocking SGK1 vivo-morpholino reduced SGK1 mRNA in the gill after transition from fresh to seawater by 66%. The IP injection of the translational blocking and splice blocking vivo-morpholinos reduced gill SGK1 protein abundance in fish transferred from fresh to seawater by 64% and 53%, respectively. Moreover, knock down of SGK1 completely eliminated the seawater induced rise in plasma membrane CFTR, demonstrating that the increase in SGK1 protein is required for the trafficking of CFTR from intracellular vesicles in mitochondrion rich cells to the plasma membrane in the gill during acclimation to seawater. This is the first report of the use of vivo-morpholinos in adult killifish and demonstrates that vivo-morpholinos are a valuable genetic tool for this environmentally relevant model organism.